Examining Text and Authorship in Translation : What Remains of Christa Wolf? - Summers, Caroline (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book, the first in-depth study of authorship in translation, explores how authorial identity is 'translated' in the literary text. In a detailed exploration of the writing of East German author Christa Wolf in English translation, it examines how the work of translators, publishers, readers and reviewers reframes the writer's identity for a new reading public. This detailed study of Wolf, an author with a complex and contested public profile, intervenes in wide-ranging contemporary debates on globalised literary culture by examining how the fragmented identity of the 'international' author is contested by different stakeholders in the construction of a world literature. The book is interdisciplinary in its approach, representing new work in Translation Studies and German Studies that is also of interest and relevance to scholars of literature in other languages.